CARDIAC REHABILITATION PROGRAM AS AN EFFORT TO IMPROVE THE QUALITY OF LIFE OF PATIENTS WITH CONgenital HEART DISEASE - Djuanda, Louis Felix; Adiwati, Erica Luis; Putri, Putu Khrisna Arsawardani (Essence of Scientific Medical Journal; Vol 22 No 1 (2024): Volume 22 No. 1 (Januari - Juni 2024) Essential: Essence of Scientific Medical Journal, 2024)
ABSTRACT   Introduction : Congenital Heart Disease (CHD) is the most common congenital disorder found throughout the world, including Indonesia. Currently, the main treatment for CHD patients is open cardiothoracic surgery. However, its implementation in Indonesia still has some obstacles due to several things which cause the life expectancy of CHD patients in Indonesia is estimated to be not as good as the life expectancy of CHD patients in developed countries. Apart from being related to life expectancy, CHD patients will also experience a decrease in their quality of life, especially those who are not treated properly. The cardiac rehabilitation program is one of the programs to overcome this. Discussion: Cardiac rehabilitation program is able to improve physical and psychosocial quality and ensure that CHD patients' cognitive and socioemotional development is maintained. Cardiac rehabilitation includes physical exercise, psychosocial management, education, risk factor modification, and nutritional management. Several studies have shown that cardiac rehabilitation has many benefits and is safe for CHD patients. In its implementation, cardiac rehabilitation faces several challenges, especially in center-based cardiac rehabilitation (CBCR), so it is recommended to increase home-based cardiac rehabilitation (HBCR) while ensuring that information regarding HBCR is delivered completely and well received by the patients. Conclusion: Based on this literature review, the authors suggest an increase in the implementation of cardiac rehabilitation for CHD patients throughout Indonesia, especially HBCR which can be carried out independently or in the community to improve the patient’s quality of life in the long term.   Keywords: congenital, cardiac, rehabilitation, quality of life